Pengaruh Work Life Balance dan Burnout terhadap Kepuasan Kerja Karyawan pada Wizzmie - Rizky Ruslan; Tenri Sayu Puspitaningsih Dipoatmodjo; Zainal Ruma; Muhammad Ichwan Musa; Khaidir Syahrul (Lembaga Pengembangan Kinerja Dosen, 2025)
This study aims to determine the effect of Work Life Balance and Burnout on Employee Job Satisfaction at Wizzmie. The method used is quantitative and uses two independent variables, namely Work Life Balance (X1), Burnout (X2) while one dependent variable is Job Satisfaction (Y). The sample used was all Wizzmie employees as many as 41 samples. The data collection techniques used in this study are primary and secondary data with data analysis in the form of instrument tests, classical assumption tests, multiple linear regression analysis, and hypothesis testing with the help of SPSS version 30. The results of this study indicate that (1) work life balance partially has a positive and insignificant effect on Employee Job Satisfaction at Wizzmie, (2) burnout partially has a negative and significant effect on Wizzmie employee job satisfaction, (3) work life balance and burnout simultaneously have a significant effect on Wizzmie job satisfaction.